OP0111 Elaboration and Preliminary Validation of the Psoriatic Arthritis Impact of Disease (PsAID) Questionnaire. A 13-Country Eular Initiative with Involvement of Patient Research Partners from Each Country. (23rd January 2014) - Gossec, L.; de Wit, M.; Heiberg, T.; Maccarone, M.; Balanescu, A.; Balint, P.; Niedermayer, D.; Cañete, J. D.; Sánchez Lombarte, A.; Helliwell, P.; Parkinson, A.; Kalyoncu, U.; et al.
Abstract : Objectives: The PsA impact of disease (PsAID) project is a EULAR initiative to elaborate a questionnaire reflecting the impact of PsA based on the patients' perception, with the involvement of patient research partners. Methods: (1) Selection of domains: Patient research partners from 11 European countries, members of the Task Force, identified 16 important domains (areas of health). In a subsequent survey, 139 patients from 13 countries prioritised the 16 domains of health according to importance. The 12 top-ranking domains were kept for the next step; 9 domains had the highest individualised priority. (2) Phrasing of questions: discussions within the group allowed the formulation of 12 numeric rating scale (NRS) questions, one for each domain. These questions were translated into 11 languages. (3) Relative importance of each domain: Relative weight of the domains was determined by asking the patients in the validation study to "spend 100 points" across the domains. This process was performed twice, once for 9 domains and once for 12 domains. The 'points' were analysed by their ranks and linearly transformed to a 0-10 scale. (4) Validation study : An international cross-sectional and longitudinal study was performed in 13 countries to examine the psychometric properties of the PsAID. Results: (a) The 12 domains of health relate both to physical and to psychological domains (e.g. pain, skin problems, fatigue but also embarrassment and/or shame with appearance, social participation and depression). The decision was taken to have 2 PsAID scores: one with 9 domains for use in clinical trials (for feasibility reasons), and one with 12 domains for use in clinical practice (to assess all the aspects important for patients). (b) Each domain is assessed by a single NRS question with a time-frame of one week. (c) A relative importance was calculated for each domain in order to combine data into a single result. The PsAID12 (clinical practice score) uses simplified weights. Pain, fatigue and skin problems are the domains with highest relative importance. (d) In all, 474 patients participated in the validation study: the population had long disease duration and moderately active disease. Correlations were, as expected, high with other patient-reported outcomes, particularly patient global (R=0.82-0.84). Test-retest reliability assessed in 71 stable patients was high (ICC, 0.94-0.95). Sensitivity to change assessed in 71 other patients 3 months after a DMARD/biologic change, was also acceptable and comparable to other outcomes (standardised response means, 0.90-0.91). Conclusions: A questionnaire to assess the impact of PsA on patients' lives has been developed and validated. Two versions of the questionnaire are available, one for clinical practice and one for clinical trials. They should allow a better assessment of the patient's perspective in PsA, but further validation is needed in other cohorts of patients and in clinical trials. Disclosure of Interest: None Declared